1988
DOI: 10.1128/aac.32.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of the novel plasmid-mediated beta-lactamase CTX-1, which confers resistance to broad-spectrum cephalosporins, and its inhibition by beta-lactamase inhibitors

Abstract: The novel ,B-lactamase CTX-1 (pl 6.3) encoded on a transferable 84-kilobase plasmid was found in six different bacterial species. It was responsible for a significant decrease in susceptibility towards most penicillins and cephalosporins, except imipenem, temocillin, and' cephalosporins which have a 7-a-methoxy substituent.Synergy between either ampicillin, piperacillin, cefotaxime, ceftazidime, or aztreonam and three D-lactamase inhibitors (clavulanic acid, sulbactam, and YTR 830) was generally found for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 12 publications
3
60
0
Order By: Relevance
“…Nucleotide sequence analysis showed that it differed from the SHV-1 sequence by three substitutions leading to the amino acid replacements Arg3Leu-205, Gly3Ser-238, and Glu3Lys-240 and by two silent mutations at positions 722 (T3C) and 796 (C3G) (positions are numbered in accordance with the coding sequence of SHV-1 [30]). These mutations are identical to those previously described for SHV-4 (22,26), except for the silent mutations.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Nucleotide sequence analysis showed that it differed from the SHV-1 sequence by three substitutions leading to the amino acid replacements Arg3Leu-205, Gly3Ser-238, and Glu3Lys-240 and by two silent mutations at positions 722 (T3C) and 796 (C3G) (positions are numbered in accordance with the coding sequence of SHV-1 [30]). These mutations are identical to those previously described for SHV-4 (22,26), except for the silent mutations.…”
Section: Resultsmentioning
confidence: 74%
“…The first nosocomial outbreaks caused by ESBL-producing strains occurred in 1985 in France (26,34). Klebsiella pneumoniae was the ESBL-producing enterobacterium most frequently isolated from clinical specimens, but E. aerogenes has recently emerged as an important hospital opportunist.…”
Section: Discussionmentioning
confidence: 99%
“…These kinetic constants, however, do not reveal that in terms of specific activity the extended-spectrum enzymes are less active than their parents by a factor of fivefold or more, so that an expanded substrate spectrum is attained at a cost of a reduced catalytic efficiency (20). (7,28) and subsequently has become established in Paris (15,16) (8,19,20,25), except for TEM-7 and SHV-5, for which relative rates at 100 ,uM substrate are shown (10,11). All enzymes had values of sO.1 with cefoxitin or imipenem as the substrate.…”
Section: Il-lactamase Propertiesmentioning
confidence: 99%
“…They have been responsible for outbreaks, particularly in intensive care units and in chronic care facilities, but have occasionally spread also to medical and surgical wards [7-131. Hospital colonisation by ESBL-producing bacteria can reflect dissemination of a few clones, or the spread of plasmids and resistance genes [13][14][15][16][17][18][19][20][21], facilitated by antibiotic pressure and inadequate infection-control practice [9-10, [22][23][24]. Several outbreaks of nosocomial infections caused by ESBL-producing K. pneumoniae occurred in our hospital between 1988 and 199 1.…”
Section: Introductionmentioning
confidence: 99%